Factors Leading to a Lack of Leisure Time in High School Students in Croatia - Lončar, Martina; Pongračić, Luka; Tonković, Aleksandra (Acta Paedagogica Vilnensia, 2024)
For a person’s overall health, it is important to establish a proper connection between work and leisure. This paper shows the results of theoretical and empirical research on factors leading to a lack of leisure time in high school students. The main goal of this paper was to determine whether high school students have any leisure time and what activities take their leisure time away. To examine this, an empirical study was conducted among 468 students in three high schools in the city of Split (general-education high school, medical high school, and electrical engineering high school). Descriptive and inferential statistics were used in the analysis. The research has shown that parents-imposed duties are minimal and do not take away a lot of students’ leisure time. On the other hand, class-related activities, i.e. homework and learning take away the greatest part of students’ leisure time, students are not prone to participate in extracurricular and out-of-school activities. Moreover, if they do engage in such activities, their choices may be influenced by gender norms.